Variable nozzle turbocharger turbine performance improvement and shock wave alternation by distributing nozzle endwall clearances. (July 2019) - Zhao, Ben; Qi, Mingxu; Sun, Harold; Shi, Xin
Effects of nozzle endwall clearances on variable nozzle turbocharger turbine performances have been widely studied, but improving the variable nozzle turbocharger efficiency utilizing an optimal distribution of nozzle endwall clearances between the hub and the shroud sides has not drawn wide attention. Meanwhile, with the various distributions, shock wave variations that are closely related to turbine reliability are rarely reported. To fill the gap, this research performed three-dimensional numerical simulations on a variable nozzle turbocharger turbine to analyze the effects of various nozzle endwall clearance distributions on both turbine performance and shock wave. The results showed that there is an optimal distribution of the nozzle endwall clearance that can improve turbine efficiency and shift nozzle trailing edge shock wave. Performed on a linear turbine nozzle and with detailed validations, both experimental measurements and numerical simulations provide evidence that supports the numerical analyses conducted on a variable nozzle turbocharger turbine.